Potential of integrating mating disruption with resistance management and stable isotope to track dispersion of lepidopteran pests - Santos, Camila Oliveira (2024)
Recent advances in organic synthesis have enabled the production of more cost-effective insect pheromone formulations for mating disruption over extensive agricultural areas. Mating disruption can interrupt the chemical communication system between males and females, safeguarding crops in treated regions. The technique can suppress Spodoptera frugiperda populations, a polyphagous lepidopteran pest causing significant global economic losses. However, validating mating disruption remains an ongoing effort. Results revealed a high percentage of mating disruption in four out of the five locations tested and a reduction in plant damage in three locations due to the pheromone application. While the crop yield was not significantly impacted, a significant decrease in ear damage was observed in treated areas. These findings highlight the potential of synthetic pheromones to disrupt mating and mitigate plant damage in maize fields infested by this pest. Escalating issues of evolution of resistance to conventional control methods in S. frugiperda increases the need for alternative approaches. Mating disruption, which affects the success of pest mating, is a potential tool to benefit resistance management. In that matter, we aimed to monitor the susceptibility of S. frugiperda populations to insecticides and Bt traits while exploring the feasibility of mating disruption as a resistance management tool. Neurotoxic insecticides demonstrated continued efficacy against the larvae despite concerns regarding potential resistance development within the benzoylurea insecticide group. Two populations exhibited incomplete resistance to the dual-gene Bt maize, which impacted various life-history population traits. We discussed the potential benefits and challenges of implementing mating disruption within insect resistance management strategies. Additionally, understanding the insect movement patterns between host plants is essential to effectively implementing these biorational pest management tools. Nitrogen-15 (15N) is a stable isotope and offers a promising tool for tracking insect dispersal among agricultural fields. Applying 15N-enriched fertilizers to specific crop areas allows plants to be labeled with a distinct isotopic signature, which can be transferred between host plants and their herbivores. The 15N levels in plant tissues were significantly higher in treatments sprayed with the isotope than in the control. The moths originating from isotope-treated plants absorbed the labeled nitrogen isotope into their tissues, although a non-significant difference was found among insects from treated and control plants. Our findings highlight the potential of integrating mating disruption with resistance management and 15N isotope tracing as feasible tools for improving our capacity to manage agricultural pests effectively. Further field trial replications should help refine and integrate these techniques into sustainable pest management programs, ensuring effective and resilient crop protection strategies. Keywords: pheromone, Spodoptera frugiperda, behavioral manipulation, insecticides and Bt crops, tracing tool, nitrogen.